Monetary policy in the context of the financial crisis : new challenges and lessons - Barnett, William A.; Jawadi, Fredj (International symposia in economic theory and econometrics ;, 2015)
ISETE 24 analyses monetary policies and central bank actions in the context of the recent global financial crisis. Part 1 discusses standard monetary policies and inflation targeting rules. Part II debates the effects of these policies and contrasts with the possible introduction of non-conventional monetary policies.